The impact of online learning among adolescents during the COVID-19 pandemic: A qualitative study of mothers' perspectives - Restuning Widiasih; Suryani Suryani; Windy Rakhmawati; Hidayat Arifin (Wolters Kluwer Medknow Publications, 2022)
Background: The COVID-19 pandemic changed the educational system from conventional learning in schools to online learning. The use of the internet as a learning medium can have positive and negative impacts on adolescents and cause concern for mothers. In this study, mothers' perspectives were explored with the phenomenological approach to assess their experience of the effect on line learning during the COVID-19 pandemic among adolescents. Materials and Methods: The qualitative study design: phenomenology was conducted on mothers with children at senior high school education levels. The data were collected using in-depth interviews from June to November 2020 in West Java, Indonesia. A total of 13 mothers were recruited using the purposive sampling technique. Data analysis was performed using the Colaizzi method and NVIVO software for managing the coding process. Results: We obtained four themes, namely (1) formation of adolescent behavior with the internet, (2) prevention of internet addiction, (3) disturbance of cognitive development, and (4) negative effect of online learning. Conclusions: The usage of the internet cannot be avoided. By guiding adolescents, the negative effects of the internet could be prevented. Developing learning programs, media, and online learning strategies according to students' needs should be promoted.